Urban heat island distribution, transformation, and projection (Case study: Jakarta City in 2000, 2020, and 2040) - Fabiola Candraningtyas Callista; Arkan Maulana Fikri; Suhardono Sapta (BIO Web of Conferences)
The Urban Heat Island (UHI) phenomenon occurs when urban areas experience higher temperatures than surrounding rural regions due to urbanization, land use changes, and reduced green spaces. In cities like Jakarta, UHI worsens climate change impacts, increases energy consumption, and threatens public health and quality of life. This study analyzes changes in UHI intensity and distribution in Jakarta between 2000 and 2020 and projects its impacts by 2040. The methodology includes analyzing Landsat satellite data to map surface temperature and land use changes, processed using geographic information system (GIS) tools. A 2040 projection is made using an urban climate model simulating temperature trends based on urbanization and land use patterns. Findings suggest that UHI intensity in Jakarta increased significantly from 2000 to 2020, particularly in densely built areas with limited green space. The 2040 projection indicates that without strong mitigation efforts, UHI will continue to rise, negatively affecting public health and increasing energy demand. However, strategies such as expanding green spaces and adopting eco-friendly building technologies can significantly reduce UHI intensity, helping mitigate climate change impacts. This research provides critical guidance for urban planners and policymakers to implement effective UHI mitigation strategies, promoting sustainable urban development and enhancing the resilience of Jakarta’s urban environment against future climate challenges.